A Scheme for Jointly Trading-off Costs and Risks of Solar Radiation Management and Mitigation Under Long-tailed Climate Sensitivity Probability Density Distributions - Elnaz Roshan; Mohammad Mohammadi Khabbazan; Hermann Held (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2020)
Side-effects of "solar-radiation management" (SRM) might be perceived as an important metric when society decides on implementing SRM as a climate policy option to alleviate anthropogenic global warming. We generalize cost-risk analysis that originally trades-off expected welfare-loss from climate policy costs and risks from transgressing climate targets to also include risks from applying SRM. In a first step of acknowledging SRM risks, we represent global precipitation mismatch as a prominent side-effect of SRM under long-tailed probabilistic knowledge about climate sensitivity. We maximize social welfare for the following three scenarios, considering alternative relative weights of risks: temperature-risk-only, precipitationrisk- only, and equally-weighted both-risks. Our analysis shows that in the temperature-risk-only scenario, perfect compliance with the 2°C-temperature target is attained for all numerically represented climate sensitivities, a unique feature of SRM, but the 2°C-compatible precipitation corridor is violated. The precipitation-risk-only scenario exhibits an approximate mirror-image of this result. In addition, under the both-risks scenario, almost 90% and perfect compliance can be achieved for the temperature and precipitation targets, respectively. Moreover, in a mitigationonly analysis, the welfare-loss from mitigation cost plus residual climate risks, compared to the no-climate-policy option, is approximately 4.3% (BGE), while being reduced to a maximum of 0.38% under a joint-mitigation-SRM analysis.
Keywords: 330; climate targets; cost-risk analysis; decision making under uncertainty; mitigation; solar-radiation management